1. The problem statement, all variables and given/known data Find $$f'(-1)$$, given $$f(y) = h(g(y)), h(2) = 55, g(-1) = 2, h'(2) = -1$$, and $$g'(-1) = 7$$. 2. Relevant equations Maybe the chain rule? 3. The attempt at a solution I thought that I could create a function given that $$g(-1)=2$$, so I thought maybe the function could be $$g(x)=-2x$$. But if I differentiate that, I get $$g'(x)=-2$$, and obviously that doesn't work since putting -1 into $$g'(x)=-2 \\ g'(-1)=-2≠7$$. I don't know what to do.